Particle triboelectric nanogenerator (P-TENG). (September 2022) - Saqib, Qazi Muhammad; Shaukat, Rayyan Ali; Chougale, Mahesh Y.; Khan, Muhammad Umair; Kim, Jungmin; Bae, Jinho
Abstract: Triboelectric nanogenerators (TENGs) have been rapidly studied for electromechanical energy scavenging and self-powered sensing. However, the limited research efforts have been devoted to utilizing tiny and irregular motions like from a human body and nature. Moreover, TENGs with multi-directional energy harnessing are rarely addressed so far. For the first time, this paper proposes a novel TENG by placing cellulose-based particles inside a rapidly degradable gelatin capsule to harvest electrical energy from all directional moving without conventional contact/separation requirements. The tiny cellulose particles (~6 µm) can generate triboelectric energy from low-frequency irregular motions, hence it is demonstrated as particle triboelectric nanogenerator (P-TENG). The proposed P-TENG device generates voltage from 15 to 85 V, current from 409 to 1326 nA, and power from 5.488 to 70 μW, when the device units increase from 1 to 16. Apart from these, the P-TENG presents maximum energy conversion efficiency up to 74.35% during vertical motion. Furthermore, it can produce energy in versatile scenarios from the various human body motions and other environmental usual movements. Hence, the proposed device can pave a new sight for low-level triboelectricity for self-powered electronic systems. Graphical Abstract: ga1 Highlights: This paper proposes a novel particle triboelectric nanogenerator (P-TENG) by placing cellulose particles inside a gelatin capsule. The proposed P-TENG can generate electrical energy from all directional moving without conventional contact/separation requirements. It achieved energy conversion efficiency up to 74.35% during vertical motion. It generated voltage from 15 to 85 V and power from 5.488 to 70 µW, when the device units increase from 1 to 16.